A Sepic-Buck Topology for Remotely Piloted Aircraft Systems Battery Charger - Rafael H. Eckstein; Eduardo V. de Souza; Maikel F. Menke; Telles B. Lazzarin (Eletrônica de Potência, 2022)
The use of remotely piloted aircraft systems (RPAS) is already a reality in applications such as geographic mapping, surveillance, digital marketing, delivery, agriculture, infrastructure inspection, and others. Most of these aircraft are purely electric, being the only source of energy, packs of ion-lithium or lithium polymer batteries. These battery packs are conceived by the association of a different number of cells, usually ranging from three cells (3S) to twelve cells (12S). However, universal battery chargers for this range are not consolidated yet due to the recent emergence of the use of RPAS for different applications. To overcome this drawback, this paper introduces a topology to charge a wide range of low voltage battery packs (3S-12S) for RPAS. The circuit is composed of two power converters, one of them is a DCM SEPIC PFC rectifi er and another is a dc-dc Buck converter. The system is design for 400 W of rated power and the proposed solution is suggested to charge battery packs from 3S to 12S.